Selection Alternative Electrical System Design at Property Mall, a Case in Ciputra World Surabaya Phase 3 - Nasychun Amin; Christiono Utomo (Institut Teknologi Sepuluh Nopember, 2019)
A superblock area has a high complexity, both in the development process and later when it is operational, so it required the right design at the beginning. At project Ciputra World phase 3, especially on the electrical system (PLN combination with generator), required the selection of appropriate design. In determining the design which will be used there are several considerations, so the decision will be made is an alternative that has the highest value. The considerations in determining the design of this project are the Initial cost, Maintenance Cost, Energy Cost. Based on the background above, the methodology to be used in determining the selection of the best design for the electrical system in Ciputra World phase 3 is a Life Cycle Cost Analysis, where the costs of each alternative will be compared. The results of research show Cost of alternative 1 about IDR 570 billion (1 PLN – Diesel Engine), Alternative 2 about IDR 555 billion (1 PLN – Diesel Engine – Gas Engine) and Alternative 3 about IDR 580 billions (2 PLN - Gas Engine). The best alternative design based on LCC is alternative 2 (1 PLN – Diesel Engine - Gas Engine)